Instalação de medidores inteligentes no Brasil: uma análise econômica - Rigodanzo, Jonas (2015)
This dissertation presents an analysis of economic viability of smart meters installation, building scenarios of probable behaviors of the residential consumers and the hourly rate which includes the concept of smart grids. The study takes account the smart meters implementation costs under the consumer point of view, using investment economic analysis concepts. The scenarios obtained from PROCEL INFO graphics and excel spreadsheets calculations compare conventional fare to different hourly rates using smart meters. From this context, it is possible observe the monthly savings that were obtained and the investments return period. The results show the investments economic viability and the priority of this new technology installation, considering that the installations shall be made first in the most viable regions. These results may turn possible a strategy that creates an order to the smart meters implementation.